2009
DOI: 10.1159/000236021
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Docetaxel with or without Gemcitabine as Second-Line Chemotherapy in Paclitaxel-Pretreated Patients with Metastatic Breast Cancer: A Randomized Phase II Study Conducted by the Hellenic Co-Operative Oncology Group

Abstract: Objective: A randomized phase II trial was conducted to test whether the addition of gemcitabine to weekly docetaxel could improve the objective response rate and survival outcomes as second-line chemotherapy in patients with metastatic breast cancer who have failed a paclitaxel-containing regimen. Methods: Patients were randomized to receive either weekly docetaxel 40 mg/m2 (group A, n = 34) or the combination of weekly docetaxel 35 mg/m2 with gemcitabine 600 mg/m2 (group B, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Taxanes is good combination agent with gemcitabine, including paclitaxel and docetaxel.To define the combination regimen including gemcitabine in MBC, physicians have conducted phase III clinical trials to compare the efficacy and toxicity between regimens MBC (Albain et al 2008 ; Chan et al 2009 ; Joensuu et al 2010 ; Zielinski et al 2005 ; Levy & Fumoleau 2005 ; Brufsky et al 2011 ; Nielsen et al 2011 ; Papadimitriou et al 2009 ).The combination of gemcitabine/taxanes-based(GT-based) combination is an effective regimen that is well tolerated with good response rates (Gudena et al 2008 ). Previous studies have demonstrated that GT-based regimen has a clinically meaningful benefit (Joensuu et al 2010 ; Nielsen et al 2011 ; Papadimitriou et al 2009 ). However, other data showed that the gemcitabine addition of taxanes was not associated with a statistically significant improvement in OR and TTP but did lead to increased toxicity (Joensuu et al 2010 ; Nielsen et al 2011 ; Papadimitriou et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Taxanes is good combination agent with gemcitabine, including paclitaxel and docetaxel.To define the combination regimen including gemcitabine in MBC, physicians have conducted phase III clinical trials to compare the efficacy and toxicity between regimens MBC (Albain et al 2008 ; Chan et al 2009 ; Joensuu et al 2010 ; Zielinski et al 2005 ; Levy & Fumoleau 2005 ; Brufsky et al 2011 ; Nielsen et al 2011 ; Papadimitriou et al 2009 ).The combination of gemcitabine/taxanes-based(GT-based) combination is an effective regimen that is well tolerated with good response rates (Gudena et al 2008 ). Previous studies have demonstrated that GT-based regimen has a clinically meaningful benefit (Joensuu et al 2010 ; Nielsen et al 2011 ; Papadimitriou et al 2009 ). However, other data showed that the gemcitabine addition of taxanes was not associated with a statistically significant improvement in OR and TTP but did lead to increased toxicity (Joensuu et al 2010 ; Nielsen et al 2011 ; Papadimitriou et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…A PRISMA flow diagram of the citation screening for the original and updated SRs is shown in Table 1 categorises included RCTs by treatment line, including key trial characteristics. Of the 14 second-and/or later-line papers, five [19][20][21][22][23] reported data for a purely second-line patient population, three [24][25][26] reported data from mixed-line treatment but provided results for the second-line subgroup separately, three [27][28][29] had unclear second-line status (i.e. it was unclear whether the previous therapy had been given in the adjuvant or metastatic setting), two [30,31] reported data from second-or later-line patients, and one [32] reported data from a second-or later-line subgroup separately.…”
Section: Resultsmentioning
confidence: 99%
“…The primary endpoint was OS in two trials [26,30], PFS in four [19,27,29,31], overall response in three [23,28,32] and not reported in five papers published between 1990 and 2000 [20-22, 24, 25] ( Table 1). Safety/toxicity was typically a secondary endpoint, amongst others.…”
Section: Outcomes Reportedmentioning
confidence: 99%
See 1 more Smart Citation
“…Four trials were excluded [8][9][10][11] , namely, a phase III trial using a three-arm design, two phase III trials without a gemcitabine-free control arm and a phase II trial without sufficient data. A total of nine trials met the inclusion criteria in this metaanalysis [12][13][14][15][16][17][18][19][20] , from which 2651 patients were included in the assessment for overall response and toxicity.…”
Section: Study Characteristicsmentioning
confidence: 99%